2015
DOI: 10.1111/asap.12097
|View full text |Cite
|
Sign up to set email alerts
|

“You Can't Give a Syringe with Unity”: Rwandan Responses to the Government's Single Recategorization Policies

Abstract: Rwanda's postgenocide government has implemented policies that resemble social psychological models of single recategorization, banning references to ethnic groups and replacing these with a superordinate, Rwandan identity. While social psychological research suggests problems with this approach, little is known about how people make sense of recategorization in the aftermath of ethnic conflict and genocide. The present interview study investigates the responses of 56 Rwandans to these single recategorization … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
25
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(26 citation statements)
references
References 67 publications
1
25
0
Order By: Relevance
“…Dressler‐Hawke () found that a higher proportion of participants in a German student sample placed responsibility for the Holocaust on the Nazis (e.g., leaders and Nazi party) than on the general population. The attribution of the genocide to “bad leaders” is also common in Rwanda among both members of the victim and perpetrator group, and part of the official narrative that is used to legitimize the restrictive post‐genocide identity policies that are in place (Moss & Vollhardt, ).…”
Section: Construals Of Collective Violence Among Victim and Perpetratmentioning
confidence: 99%
See 1 more Smart Citation
“…Dressler‐Hawke () found that a higher proportion of participants in a German student sample placed responsibility for the Holocaust on the Nazis (e.g., leaders and Nazi party) than on the general population. The attribution of the genocide to “bad leaders” is also common in Rwanda among both members of the victim and perpetrator group, and part of the official narrative that is used to legitimize the restrictive post‐genocide identity policies that are in place (Moss & Vollhardt, ).…”
Section: Construals Of Collective Violence Among Victim and Perpetratmentioning
confidence: 99%
“…Similarly, qualitative research in the aftermath of the Rwandan Genocide showed that the goal of developing the country was one way in which some participants justified the policy in Rwanda that ban the use of the ethnic labels (Hutu and Tutsi) that were implicated in the Rwandan Genocide. Other participants experienced this policy as a lack of acknowledgment of their history of victimization (Moss & Vollhardt, ). When rebuilding is seen as a more immediate group goal than commemoration of victimization, the narrative may shift accordingly.…”
Section: Construals Of Collective Violence Among Victim and Perpetratmentioning
confidence: 99%
“…This participant takes a neutral stance but insists that once the ethnic groups are maintained, care must be taken that they are not used to discriminate against some. This caveat reminds us that ethnic groups have been manipulated by the leaders of two former political regimes and corresponds to the version of icially conveyed by the current Rwandan government (Moss & Vollhardt, 2015).…”
Section: Separating Hutus Perpetrators From Hutus Non-perpetratorsmentioning
confidence: 89%
“…Participant No. 9 raised arguments corresponding to those in the of icial version of the policy, that the distinction between Hutus and Tutsis is only arti icial (Moss & Vollhardt, 2015).…”
Section: Challenging Ethnic Groupsmentioning
confidence: 99%
“…
This commentary on Moss and Vollhardt's (2016) article examines how their findings complement a study by Kanazayire, Licata, Mélotte, Dusingizemungu, and Azzi (2014), which also sought to assess the effectiveness of the Rwandan government's ethnic identity policy for improving reconciliation sentiments in postgenocide Rwanda.Moss and Vollhardt's article (2016)--"You can't give a syringe with unity": Rwandan responses to the government's single recategorization policies"-provides a precious insight on the way Rwandan people construe, and take positions toward, their government identity policy.This qualitative study based on face-to-face interviews conducted in Rwanda ventures beyond the usual setting in contrast of the two ethnic (or pseudoethnic) identities involved in the 1994 genocide. In that respect, it brings a welcome complement to existing studies.
…”
mentioning
confidence: 99%